Study of the drying kinetics for apples in a convective drier - Cruz, AC (2012)
In the present work a convective drier was used to dehydrate apple slices up to a moisture content of less than 2 % (wet basis), so as to obtain a crunchy apple snack. Two commercial varieties were tested, namely Golden and Smith. The drier was operated at different temperatures, 30, 40 50 and 60 ºC, and the moisture content of the product was calculated based on the mass, which was registered by means of a data logger, throughout the whole trial. The kinetic data was then treated and fitted to different thin layer models frequently cited in literature, which were: Page, Henderson and Pabis, Logarithmic and Vega-Lemus. Others were also tested, but convergence was not achieved. For the fitting software SigmaPlot V8.0 (SPSS, Inc.) was used, and to evaluate the quality of the estimations the correlation coefficient (R) and the standard error of the estimate (SEE) were determined From the models tested it was possible to see that the Vega-Lemus was the worst to describe the drying kinetic in the present case, on the other hand, the best model was the Page. Also the Fick’s equation for diffusion was used to estimate the diffusivities at different temperatures, and from those to estimate the activation energy for moisture diffusion, which was found to be 35 kJ/mol for the drying of apples from Golden variety and 33 kJ/mol for the Smith variety.